Specific adsorption of tetracycline from milk by using biocompatible magnetic molecular imprinting material and evaluation by ECD. (1st October 2020) - Wang, Shu-Xian; Ma, Rong-Rong; Mazzu, Ying Z.; Zhang, Jia-Wei; Li, Wei; Tan, Ling; Zhou, Lian-Di; Xia, Zhi-Ning; Zhang, Qi-Hui; Yuan, Chun-Su
Highlights: BMMIPs possess biocompatibility and specific adsorption capacity for tetracycline. Zein is an optimal choice for the raw material of BMMIPs. The application of BMMIPs combined with ECD is valuable for practical application. Abstract: Biocompatible magnetic molecularly imprinted polymers (BMMIPs) were prepared with Zein for the first time, and were used to enrich tetracycline compounds selectively. Innovative combination of BMMIPs and electrochemistry to obtain lower detection line to satisfy industrial detection demands. Using Zein as the crosslinking agent, the polymers were synthesized on the surface of Fe3 O4 particles. The scanning electron microscope, transmission electron microscope and X-ray diffraction technologies were used to characterize BMMIPs. Through optimization, BMMIPs attained large adsorption capacity (236.40 mg/g) with fast kinetics (40 min) and followed the Langmuir isotherm and pseudo-second-order kinetic models. BMMIPs had good recognition ability, the selective factors of oxytetracycline, chlortetracycline, doxycycline were 4.78, 4.23, and 3.39, respectively. Excellent linearity was attained in the range of 0.025–500 μg/mL, with low detection limits and low quantitation limits of 0.025 and 0.083 μg/mL. According to our exploring, BMMIPs was ideal materials for enrichment of tetracycline in complex biological samples.